An Exploration into the World of Secretaries and Administrative Assistants - Ngotngamwong, Rachaniphorn (Business Administration and Management Journal Review, 2018)
Secretaries and Administrative Assistants play significant roles in each and every organization. Despite the general stereotype of their professions, one can never fully understand the extent of their work, particularly so when technology and time have transformed their roles over the past decades. This explorative qualitative study, attempted to dig a little deeper into the professional lives of ten secretaries and administrative assistants through in-depth interviews from different industries. Out of the ten participants, up to 90% were female, with only 10% represented by the male gender. Services were rendered to top management, and contacts were made both internally and externally to accomplish task assignments. The majority performed secretarial duties while 20% were involved in other non-secretarial duties as well. Most secretaries enjoyed their work and expressed three areas in which they enjoyed and least enjoyed in their careers, as well as challenges encountered on the job. The enjoyment included working with nice bosses, the contacts made, and being entrusted decision-making. They were however, unhappy with the negative perceptions people had of them, working with jerks, and work pressures. Although the majority were satisfied with their jobs, up to 40% stated that they would like to move to other professions if given the opportunity.